Заговоры как пример веры в магию слова и её использования в культуре древних славян = Spells as the examples of faith in the magic of word in the culture of ancient Slavs - Nowaczyk, Marta (Journal of Education, Health and Sport, 2016)
Marta Nowaczyk. Заговоры как пример веры в магию слова и её использования в культуре древних славян. Spells as the examples of faith in the magic of word in the culture of ancient Slavs. Journal of Education, Health and Sport. 2016;6(9):983-992. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.226226 https://pbn.nauka.gov.pl/sedno-webapp/works/774022 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Pola nd Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License ( http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.08.2016. Revised 20.09.2016. Accepted: 26.09.2016. Marta Nowaczyk[1] doktorantka - językoznawstwo Wydział Humanistyczny, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Заговоры как пример веры в магию слова и её использования в культуре древних славян Spells as the examples of faith in the magic of word in the culture of ancient Slavs Abstract Nowadays, the ritual sphere is pushed to the margins of the human consciousness. For the general public it is only associated with superstitions, while the linguists link it with its magical function. The faith of the ancient slavs considered “the word” as a material unit. The titled spell is handed down from a generation to generation with the use of texts, which constituted one of the first literary genre of the folk prose. In this article this literary genre was presented as part of the rituals and the role of these texts was noted in the people’s lives. Among the ancient slavs, there was a deep belief in the magical power of a word and circumspection in the use of the language. The author discusses the structure of spells and subdivides them. Furthermore, he draws attention to the heroes of these magic formulas. Closely related to the topic of spells are also the ‘professions’ earning their living from them, which was also pondered in this article. Keywords: spells, word, ancient slavs, wizard, faith, heathen Абстрактные В сегодняшнее время ритуальная сфера остаётся как будто на полях человеческого сознания. В обществе ассоцируется с суевериями, а среди языковедов соединяется с магической функцией. Древние славяне считают «слово» материальной единицей. Заглавные заговоры – это передаваемые из поколения в поколение тексты, составляющие один из первых жанров народной прозы. В статье представлено этот жанр как элемент ритуалов а также подчёркнуто роль этих текстов в жизни людей. Среди древних славян существовала вера в магическую силу слова и осторожный подход к языку. Автор анализирует структуру заговоров а также проводит их деление. Кроме того автор обращает внимание на персонажей магических формул. С темой заговоров тесно связаны и профессии и люди, занимающиеся словесными ритуалами, на что также намекает статья. КЛЮЧЕВЫЕ СЛОВА: заговор, слово, язычники, древние славяне, колдуны, вера [1] mgr Marta Nowaczyk, doktorantka – językoznawstwo, e-mail: ufcia007@wp.pl